Assessing the cost efficiency of raw materials inventory using the economic order quantity method - Herlambang; Nanda Sekar Ayu (Priviet Social Sciences Journal, 2021)
This study aims to assess the cost efficiency of raw material inventory using the Economic Order Quantity (EOQ) method at PT. XYZ. The data used in this study is documentation such as data on product orders for raw materials, lead time data for raw materials, and Safety Stock data for raw materials, average purchase data for product raw materials, purchase cost data, storage costs and ordering costs for raw materials. products, interviews and observations to related parties such as staff assistant managers, with supervisors Planning Production and Inventory Control regarding inventory in the raw material warehouse. The type of research used is a case study, where the research is carried out intensively in detail and in depth on an object under study. This research method is interview and documentation method. The variables in this study are inventory and use of raw materials. The analysis used is the Economic Order Quantity method. The results of this study indicate that the conditions in the supply of raw materials at PT. XYZ is not good. It can be seen from the frequent shortage of raw materials for the production process, so orders are not on time. Therefore, PT. XYZ controls the inventory of raw materials by storing raw material reserves, so that production continues and is not hampered